2023
DOI: 10.1080/13880209.2022.2158349
|View full text |Cite
|
Sign up to set email alerts
|

Advances for pharmacological activities of Polygonum cuspidatum - A review

Abstract: Context Polygonum cuspidatum Sieb. et Zucc (Polygonaceae), the root of which is included in the Chinese Pharmcopoeia under the name ‘Huzhang', has a long history as a medicinal plant and vegetable. Polygonum cuspidatum has been used in traditional Chinese medicine for the treatment of inflammation, hyperlipemia, etc. Objective This article reviews the pharmacological action and the clinical applications of Polygonu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 86 publications
(91 reference statements)
0
8
0
Order By: Relevance
“…They found that crude extract obtained from the leaves of Brucea antidysenterica induces cell death mediated by caspases on drug-resistant cancer cells, such as CCRF-CEM, a human leukemia cell line, at a low concentration (from 12.42 µg mL −1 to 38.70 µg mL −1 ). Other authors reported that ethanol extracts of P. cuspidatum demonstrated efficacy on the loss of viability of cells in oral, breast, and ovarian cancer at lower concentrations, EC 50 : <50 µg mL −1 [ 17 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that crude extract obtained from the leaves of Brucea antidysenterica induces cell death mediated by caspases on drug-resistant cancer cells, such as CCRF-CEM, a human leukemia cell line, at a low concentration (from 12.42 µg mL −1 to 38.70 µg mL −1 ). Other authors reported that ethanol extracts of P. cuspidatum demonstrated efficacy on the loss of viability of cells in oral, breast, and ovarian cancer at lower concentrations, EC 50 : <50 µg mL −1 [ 17 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Emodin is an anthraquinone located in the rhizome, and quercetin is a flavonoid in leaves and stems. Polyphenols are commonly found in flowers [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Polygonum cuspidatum has the ability to clear heat and detoxify the body and is commonly used to treat lungheating coughs. [8][9][10][11] In the COVID-19 epidemic, P cuspidatum was widely used and its use was recognized by the Chinese medicine community. [11,12] Modern pharmacological studies have shown that the various active ingredients in P cuspidatum mainly include anthraquinones, flavonoids, phenols and other compounds, which have antibacterial, antiviral, antioxidant and microcirculatory improving effects.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11] In the COVID-19 epidemic, P cuspidatum was widely used and its use was recognized by the Chinese medicine community. [11,12] Modern pharmacological studies have shown that the various active ingredients in P cuspidatum mainly include anthraquinones, flavonoids, phenols and other compounds, which have antibacterial, antiviral, antioxidant and microcirculatory improving effects. [13][14][15][16] However, the specific mechanism of action by which P cuspidatum exerts its value during epidemics is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Polygonum cuspidatum (Pc) primarily comprises polydatin, resveratrol, emodin, quercetin, and their derivatives as principal bioactive phytochemical components. The therapeutic and preventive effects of Pc against various human diseases have been extensively investigated [ 1 ]. The anti-inflammatory, antioxidant, antiviral, and antimicrobial properties of Pc have been validated in cultured cell lines and animal models [ 1 ].…”
Section: Introductionmentioning
confidence: 99%